2017
DOI: 10.17943/etku.305062
|View full text |Cite
|
Sign up to set email alerts
|

Bi̇li̇şi̇m Teknoloji̇leri̇ Öğretmen Adaylarinin Bakiş Açisindan 21. Yüzyil Öğrenen Ve Öğretmen Özelli̇kleri̇

Abstract: Bu çalışmanın amacı Bilişim Teknolojileri öğretmen adaylarının bakış açısından 21. yüzyıl öğrenenlerinin ve öğretmenlerinin özelliklerini irdelemek ve farkındalıklarını belirlemektir. Bu amaçla 63 öğretmen adayının öğretmenlik uygulaması dersi kapsamında ağ günlüklerine "21. yüzyıl öğrencisinin ve öğretmeninin özellikleri" başlığı altında yazdıkları yazılar doküman analizi ile çözümlenmiştir. Analiz sonucunda öğretmen adaylarının 21. yüzyıl öğrenen ve öğretmen özellikleri olarak belirttikleri niteliklere ilişk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The reasons for the inconsistency between the finding of the current study and that of Yesilyurt (2010) may be because Yesilyurt's sampling is dominated by the students of Technical Education Faculty most of whose student population is made up of male students. In the research of Daghan et al (2017), pre-service teachers stated that the learners of the 21 st century should have collaborative working skills. No significant difference was found depending on the gender variable in the sub-dimensions of "cognitive skills", "autonomous skills", "innovativeness skills" and "flexible teaching skills".…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The reasons for the inconsistency between the finding of the current study and that of Yesilyurt (2010) may be because Yesilyurt's sampling is dominated by the students of Technical Education Faculty most of whose student population is made up of male students. In the research of Daghan et al (2017), pre-service teachers stated that the learners of the 21 st century should have collaborative working skills. No significant difference was found depending on the gender variable in the sub-dimensions of "cognitive skills", "autonomous skills", "innovativeness skills" and "flexible teaching skills".…”
Section: Discussionmentioning
confidence: 99%
“…This finding shows that the pre-service teachers with lower academic achievement have inadequate awareness of the processing and coding of information through cognitive processes and of the outputs emerging as a result of the operations taking place in mental processes. Daghan et al, (2017) found that among 21 st century skills most strongly emphasized by the pre-service teachers come cognition-based skills to the fore. Doganay and Demir (2011) found that in all the dimensions of cognitive awareness, the cognitive awareness levels of the pre-service teachers having higher academic achievement were found be significantly higher than those of the pre-service teachers with lower academic achievement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…How to develop 21 st century learning skills comes with the question of how to organize learning environments for 21 st century individuals (Dağhan, Kibar, Çetin, Telli, & Akkoyunlu, 2017). This situation raises the question concerning the role of school in students' development of these skills.…”
Section: Introductionmentioning
confidence: 99%